Pityriasis versicolor in two 8-year-old monozygotic twins. - Milano, A. (European Journal of Pediatric Dermatology, 2011)
There are not other cases in the literature of monozygotic twins affected by pityriasis versicolor in the prepubertal age. According to the few genetic studies on this topic (1) pityriasis versicolor starts earlier in subjects with positive family history.